Shear Wave Elastography and Shear Wave Dispersion for Assessing Fibrosis and Inflammation of Liver Tissue in Children with Juvenile Autoimmune Liver Diseases - Maryna Dyba; Valentyna Berezenko (Biomedical and Biotechnology Research Journal, 2025)
Background: The purpose of the study is to evaluate the potential of two-dimensional shear wave elastography (2D-SWE) and two-dimensional shear wave dispersion (2D-SWD) to determine the fibrosis stage and inflammation degree of liver tissues in children with juvenile autoimmune liver disease (JALD). Methods: This study comprised 42 patients with a mean age of 11 years (range: 9–14 years) with JALD who underwent liver biopsies. We compared the parameters of 2D-SWE and 2D-SWD with the histological stage of liver fibrosis using the Metavir score, histological index of inflammatory activity (HAI) grade using the modified Knodell score, and biochemical indicators of inflammation. A multivariate linear regression analysis was performed to identify factors that significantly affected 2D-SWE and 2D-SWD values. Results: Most children (85.7%; n = 36) exhibited stage ≥F2 liver fibrosis according to the Metavir score and HAI grade ≥3 (76.2%; n = 32). The receiver-operating characteristic (ROC) curve indicated the acceptable discrimination of 2D-SWE for stage ≥F3 liver fibrosis. The 2D-SWE cutoff value ≥8.9 kPa yielded 71% sensitivity and 72% specificity for significant fibrosis (stages F3-F4). The ROC curve demonstrated the excellent discrimination of 2D-SWD for HAI grade ≥3. Conclusion: The 2D-SWD cutoff value ≥16.35 m/s/kHz yielded 85% sensitivity and 86% specificity for moderate and severe hepatitis in liver tissues of children without cirrhosis. 2D-SWE demonstrated good performance in diagnosing advanced fibrosis in children with JALD. In addition, 2D-SWD was shown to be a method for assessing liver inflammation and can be used to diagnose moderate-to-severe hepatitis in children with JALD.